DESIGN AND IMPLEMENTATION OF AN APPRAISAL SYSTEM - Teo, Kah Hua (2007)
This dissertation seeks to research, design and implement an educated simple performance management system in Singapore Epson Manufacturing Pte Ltd. Currently not even a formal performance appraisal process present. The employees are simply given a grade at the end of year depicting their performance, with no discussion whatsoever.